Hospital Staffing Decisions: Does Financial Performance Matter? - Mei Zhao; Gloria J. Bazzoli; Jan P. Clement; Richard C. Lindrooth; JoAnn M. Nolin; Askar S. Chukmaitov (SAGE Publishing, 2008)
This study assesses the impact of changes in hospitals' financial conditions on changes in hospitals' staffing decisions. The sample consisted of community hospitals operating between 1995 and 2000. The analysis employed a generalized method of moments (GMM) estimator for its dynamic panel data. Cash flow and patient margin were used to measure financial condition. We estimated the effect of changing financial condition on the number of full-time equivalent personnel (FTEs), registered nurses (RNs), and licensed practical nurses (LPNs) per 1,000 adjusted patient days. Our results suggest that declining financial performance led to cutbacks in LPN FTEs per adjusted patient day, but the effects on total hospital FTEs and RN FTEs were mixed.